Porosity–Acidity Interplay in Hierarchical ZSM‐5 Zeolites for Pyrolysis Oil Valorization to Aromatics. Issue 19 (4th September 2015) - Puértolas, Begoña; Veses, Alberto; Callén, Maria Soledad; Mitchell, Sharon; García, Tomás; Pérez‐Ramírez, Javier
Abstract The properties of crude bio‐oils attained by the pyrolysis of lignocellulosic biomass can be greatly enhanced by means of catalytic upgrading. Here, we demonstrate an efficient process concept coupling the production of pyrolysis oil from pine wood with a consecutive catalytic upgrading step over hierarchically structured ZSM‐5 zeolites to attain aromatic‐rich bio‐oils. The selective upgrading of these complex mixtures is shown to be tightly connected to the extent of mesopore development and the density of Brønsted acid sites at the mesopore surface. A full product analysis enables elucidation of the impact of mesopore introduction and the acidic properties on the complex reaction network. The preferential occurrence of decarbonylation reactions in hierarchical zeolites versus dehydration transformations in the bulk counterparts is believed to be decisive in promoting increased aromatics formation.